2007
DOI: 10.1111/j.1540-8175.2007.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Right Heart Function and Scleroderma: Insights from Tricuspid Annular Plane Systolic Excursion

Abstract: We can predict the rehospitalization rate of SSc patients by TAPSE and RVEF, suggesting the involvement of heart, skin, lung, and other organs in scleroderma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…14,15 There has been a wide range of correlations between TAPSE and other measures of RV function. Good correlations were obtained comparing TAPSE with RVEF, [16][17][18][19][20] and better correlations were obtained comparing TAPSE with RV fractional area of change 6,12 and global RV strain. 21 Correlations were more modest when compared with RVEF using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 89%
“…14,15 There has been a wide range of correlations between TAPSE and other measures of RV function. Good correlations were obtained comparing TAPSE with RVEF, [16][17][18][19][20] and better correlations were obtained comparing TAPSE with RV fractional area of change 6,12 and global RV strain. 21 Correlations were more modest when compared with RVEF using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 89%
“…TAPSE has been shown to predict morbidity and mortality in patients with PAH and has become a recommended method for measuring the efficacy of PH medical therapy in PAH. 11,13,14 Previous work has shown that longitudinal RV shortening accounts for approximately 80% of global RV function in normal subjects and that longitudinal function represents the afterload-responsive element of right heart function in subjects with PAH treated with PH medical therapy. 9 Until now, TAPSE has been thought of as a method specific to RV function, with the direct or indirect role of RA function not known.…”
Section: Resultsmentioning
confidence: 99%
“…RV systolic function can be assessed by measuring the longitudinal systolic displacement of the RV base toward the RV apex. This is commonly referred to as the tricuspid annular plane systolic excursion (14) and is relatively simple to perform, highly reproducible, and has been shown to correlate well with RV ejection fraction derived from radionuclide angiography (14,15). A normal tricuspid annular plane systolic excursion is about 2.4-2.7 cm (16,17), whereas a value below 1.8 cm has been shown to have an 87% accuracy at predicting a stroke volume index less than 29 ml/m 2 (18).…”
Section: Detection and Monitoring Of Rv Function In Critically Ill Pamentioning
confidence: 99%